2015
DOI: 10.3389/fmicb.2015.00729
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity differences along an epigenic cave stream reveal evidence of community dynamics, succession, and stability

Abstract: Unchanging physicochemical conditions and nutrient sources over long periods of time in cave and karst subsurface habitats, particularly aquifers, can support stable ecosystems, termed autochthonous microbial endokarst communities (AMEC). AMEC existence is unknown for other karst settings, such as epigenic cave streams. Conceptually, AMEC should not form in streams due to faster turnover rates and seasonal disturbances that have the capacity to transport large quantities of water and sediment and to change all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
2
14
1
1
Order By: Relevance
“…However, we did find significant differences among bacterial communities in terms of their occupied niches (i.e., air, rock, sediment, and water), not unlike Brannen-Donnelly and Engel (2015) who reported that bacterial community composition in cave streams and sediments differed at the class level. More recently, Alonso et al (2018) reported that mineral substrate was the most significant factor determining cave microbial diversity and structure.…”
Section: Discussioncontrasting
confidence: 99%
“…However, we did find significant differences among bacterial communities in terms of their occupied niches (i.e., air, rock, sediment, and water), not unlike Brannen-Donnelly and Engel (2015) who reported that bacterial community composition in cave streams and sediments differed at the class level. More recently, Alonso et al (2018) reported that mineral substrate was the most significant factor determining cave microbial diversity and structure.…”
Section: Discussioncontrasting
confidence: 99%
“…These sites were chosen based on oligotrophic conditions, sampling of pelagic microbial communities, and 454-pyrosequencing. These comparative samples included: the Edwards karst aquifer of Texas (Edwards aquifer; SRP010407; Engel and Randall, 2011 ); a shallow karst aquifer in Germany (Limestone aquifer; ERP020663; Herrmann et al, 2017 ); stream water in a Kentucky epigenic cave (Cascade Cave system; SRP058014; Brannen-Donnelly and Engel, 2015 ); and a surface lake open to photosynthetic input (the oligotrophic Lake Brienz; SRP021556; Köllner et al, 2013 ; Figure 5A ). Analyses are therefore based on sequencing method (454-pyrosequencing), PCR primers and average number of amplicons.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the first indications of organic structures became visible (e.g., 12 months). The scale bars indicate the extent of magnification investigations of stagnant cave pools in the epiphreatic zone of a karst system (Shabarova et al, 2013(Shabarova et al, , 2014Shabarova & Pernthaler, 2010) and an epigenic cave stream (Brannen-Donnelly & Engel, 2015) indeed indicated the presence of stable and transient bacterial populations. For example, Shabarova et al (2014) defined a bacterial "core" assemblage as the subset of those bacterial genotypes that were present in all samples during their temporal study of the bacterial community development in stagnant rock pools.…”
Section: Defining the Amec Versus Tmec Conceptmentioning
confidence: 99%
“…The aim of this concept is to predict the proportion of AMEC versus TMEC and its typical range of variation in spring water according to the catchment and the hydrogeology of the investigated system. To facilitate its correct understanding and interpretation (Brannen‐Donnelly & Engel, ; Wilhartitz & Farnleitner, ), the concept is described in more detail in the following section. Microbes that are unable to proliferate and unable to form stable populations within the karst aquifer are considered TMEC.…”
Section: Occurrence Of Microbial Communities In Spring Water Of Alpinmentioning
confidence: 99%